Design safety considerations for water cooled small modular reactors incorporating lessons learned from the Fukushima Daiichi accident. (IAEA-TECDOC, 2016)
"This publication presents technology developers and users with common considerations, approaches and measures for enhancing the defense in depth and operability of water cooled small modular reactor (SMR) design concepts to cope with extreme natural hazards. Indicative requirements to prevent an accident such as the Fukushima Daiichi accident from recurring are also provided for States planning to adopt water cooled SMR designs and technologies. This publication was produced within the framework of the IAEA Action Plan on effectively utilizing research and development."--Publisher's description.